Investigation of coupled effects of temperature and relative humidity on dynamic performance of MEMS beam resonators in gas rarefaction - Cuong, Nguyen Chi; Thang, Trinh Xuan; Phat, Truong Van; Giap, Vu Manh; Thanh, Ngo Vo Ke (Vietnam Journal of Science and Technology, 2019)
The modified molecular gas lubrication (MMGL) equation with the effective viscosity of moist air is utilized to solve for the squeeze film damping (SFD) problem on the dynamic performance of MEMS cantilever resonators. Thus, the coupled effects of temperature and relative humidity are discussed on the Q-factors of MEMS cantilever resonators in a wide range of gas rarefaction (pressure, p and accommodation coefficients, ACs) and resonant mode of vibration. The results showed that the Q-factor of moist air decreases more significantly as temperature and relative humidity increase at higher gas rarefaction (lower p, and ACs) conditions.